Planning the Square Area as a Public Space: Realizing Green Open Space in Asahan Regency - Agung Pribadi; Abdi Sugiarto (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to examine the Planning of the Square Area as a Public Space: Realizing Green Open Space in Asahan Regency. This research adopts a qualitative approach, which aims to gain a deep understanding of the perceptions, needs, and expectations of the community and related parties towards the development of the square as a green open space (RTH). A comprehensive overview of the qualitative methods used in the research, as well as data collection and analysis techniques that will be applied to explore the perceptions, needs, and expectations of the community towards the development of the square as a green public space in Asahan Regency. Research Results The presence of green open spaces such as squares can contribute to improving environmental quality, such as improving air quality, reducing micro-temperatures, and protecting biodiversity. In addition, attractive squares can also increase tourist attractions, which has a positive impact on the local economy. By considering all of the above aspects, the planning of the square area as a public space in Asahan Regency will not only create quality green open space, but will also contribute to better social, economic, and environmental development. It is hoped that this initiative can be realized with the support of all parties, including the government, the community, and other stakeholders, to create a better environment for future generations.